Two new species of the genus Blattochaeta Reitter, 1910 (Insecta, Coleoptera, Leiodidae, Cholevinae, Leptodirini) from Montenegro - Čeplík, Dávid; Lakota, Ján; Čeplík, Jaroslav (Zootaxa, 2021)
Two further new species of the tribe Leptodirini Lacordaire, 1854 inhabit the subterranean world of the Southern Dinarides located in the northern and southeastern mountains of Montenegro: Blattochaeta brankojalzici D. Čeplík, Lakota & J. Čeplík, sp. nov., and Blattochaeta peterhlavaci D. Čeplík, Lakota & J. Čeplík, sp. nov. The new species are described, illustrated and dedicated to our dear friends in the field of subterranean biology and entomology. Morphological comparison with available related species, as well as the distribution, including a map for the whole genus Blattochaeta Reitter, 1910, and information on their natural history are given. A catalogue for the whole genus is provided and some taxonomic problems of related species are indicated.